Pengaruh Pengembangan Sumber Daya Manusia dan Budaya Organisasi Terhadap Human Capital Strategy pada Start up Sektor Bisnis Education Technology di Indonesia - Mugi Puspita; Rian Japesa (In Search (Informatic, Science, Entrepreneur, Applied Art, Research, Humanism), 2024)
This research aims to examine the influence of human resource development and organizational culture on human capital strategy in education technology start-ups in Indonesia. Data research techniques use descriptive and verification methods with the Smart-PLS application. This research is included in non-experimental research (survey), where survey research conducts a study of the population by selecting samples from that population. The research sample consisted of 53 start-up education technology companies in Indonesia. The research results show that HR development has an influence on human capital strategy. Organizational culture has no influence on human capital strategy.